2022
DOI: 10.1177/00469580221096259
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Identification of Key Genes for the Development and Prognosis of Lung Adenocarcinoma

Abstract: Objective: Lung adenocarcinoma (LUAD) is a common malignant tumor with a poor prognosis. The present study aimed to screen the key genes involved in LUAD development and prognosis. Methods: The transcriptome data for 515 LUAD and 347 normal samples were downloaded from The Cancer Genome Atlas and Genotype Tissue Expression databases. The weighted gene co-expression network and differentially expressed genes were used to identify the central regulatory genes for the development of LUAD. Univariate Cox, LASSO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…It has also been found to be essential for fetal liver development in zebrafish and acts as an antiapoptotic protein in Hela or HepG2 cells [ 6 ]. Interestingly, recent studies have suggested that SNX7 may have potential value in clinical prediction of lung cancer [ 9 , 10 ], which is similar to our observations in HCC. Here, we analyzed and confirmed that both the mRNA and protein levels of SNX7 are significantly higher in HCC, which is strongly correlated with the pathologic stage of the disease and can serve as an independent risk factor for HCC patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has also been found to be essential for fetal liver development in zebrafish and acts as an antiapoptotic protein in Hela or HepG2 cells [ 6 ]. Interestingly, recent studies have suggested that SNX7 may have potential value in clinical prediction of lung cancer [ 9 , 10 ], which is similar to our observations in HCC. Here, we analyzed and confirmed that both the mRNA and protein levels of SNX7 are significantly higher in HCC, which is strongly correlated with the pathologic stage of the disease and can serve as an independent risk factor for HCC patients.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, one study developed a predictive model for recurrence in early-stage lung adenocarcinoma, incorporating SNX7 alongside other epithelial-to-mesenchymal transition-related genes (AGL, ECM1, ENPP1, SNX7, and TSPAN12) [ 9 ]. Another study identified SNX7 as an unfavorable prognosis gene in lung adenocarcinoma [ 10 ]. Nevertheless, the clinical value of its diagnosis, prognosis, and prediction of susceptibility to drug therapy in HCC has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the biological processes of lung adenocarcinoma and glioma are mainly enriched in extracellular structural tissue, external encapsulated structural tissue, and extracellular matrix tissue [ 22 , 23 ]. Molecular functions in bladder cancer studies have been mainly concentrated in channel activity, passive transmembrane transporter activity, and gated channel activity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“… 339 In several studies, PCSK9 has been identified as a critical gene associated with unfavorable prognoses in lung adenocarcinoma. 334 , 350 , 351 Elevated PCSK9 expression has also been reported to be instrumental in promoting the metastasis and invasiveness of lung cancer and melanoma (specifically within the lung). 352 , 353 In addition, a clinical cohort study involving 44 elderly patients with non-small-cell lung cancer (NSCLC), who were treated with the ICI, nivolumab, revealed that NSCLC patients with lower levels of blood PCSK9 ( < 95 ng/mL) enjoyed a significantly prolonged OS during the second therapeutic cycle.…”
Section: The Role Of Pcsk9 In Various Disordersmentioning
confidence: 99%